Physicochemical characteristics and fatty acid profile of meat from lambs with different genotypes and diets - Roberto Germano Costa (Revista Brasileira de Zootecnia, 2015)
The objective of this study was to evaluate the chemical composition and fatty acid profile of meat from Santa Inês, Dorper × Santa Inês, and undefined-breed lambs finished in a feedlot system according to two forage:concentrate ratios (50:50 and 20:80) in the diet. Overall, 54 non-castrated animals were used (with an average initial weight of 23±1.5 kg at 150 days old) and were slaughtered when they reached 36 kg of live weight or 63 days of confinement. Diets with high concentrate levels favored meat production with higher protein content. Among the saturated fatty acids, only heptadecanoic (C17:0) and arachidic acids (C20:0) differed among the treatments. The amount of oleic acid detected in the meat ranged from 49.2 to 51.9 g/100 g, making this one the most representative fatty acids. Regardless of the diet and genotype, the unsaturated fatty acid and desirable fatty acid levels in the lamb meat characterize it as of satisfactory quality for the consumer market.